Theatre Excursion: Circuit of Culture of Production and Consumption of Traditional Theatre - Afri Wita; Apip Apip (LP2M ISBI Bandung, 2020)
This paper is aimed at studying the production and consumption of traditional theatre. The study is conducted within cultural studies perspective using Circuit of Culture. In the production layer the focus of the analysis will be on how the traditional theatre is produced either technically or culturally. While on the consumption, the analysis will be on the audience involving in this cultural product. The object of the study is the traditional theatre performed in Rumentang Siang Bandung. The study reveals that the practice of theatre excursion perpetuates production of traditional theatre and presents the consumption space for the audience of traditional theatre. The herds of school students organized by their teachers are having theatre excursion under the program of Taman Budaya to arouse appreciation toward tradition. The circuit of culture of traditional theatre in the context of production and consumption is articulated through the theatre excursion